Theoretical model of absorption coefficient of an inhomogeneous MPP absorber with multi-cavity depths. (March 2019) - Mosa, Ali Ibrahim; Putra, Azma; Ramlan, Roszaidi; Prasetiyo, Iwan; Esraa, Al-Ameri
Abstract: Micro-perforated panel (MPP) absorber has been known as an alternative absorber to classical porous material given its facile installation, long durability, environmental friendliness and attractive appearance. Extensive studies of MPP absorber proposing the improvement of its absorption frequency bandwidth have been published. This study presents a MPP absorber introduced with inhomogeneous perforations and with multi-cavity depths. The MPP is divided into two sub-area, where each area has different hole diameter, perforation ratio and a separated backed cavity depth. The acoustic impedance is modelled using electrical equivalent circuit and the absorption coefficient is calculated under normal-incidence of sound. It is found that the inhomogeneous MPP can have good bandwidth of absorption by designing the sub-MPP of smaller perforation ratio with large hole diameter and the one having the larger perforation ratio with smaller hole diameter. The absorption bandwidth can be conveniently controlled by adjusting the cavity depth of each sub-MPP. The results from the experimental work show good agreement with the theoretical model.